ETNOMATEMATIKA MASYARAKAT PANDALUNGAN DESA SUMBER KALONG PADA MATERI PERBANDINGAN SENILAI - Ma’asyi, Suhulatul; Lutfiyah, Lutfiyah; Anas, Aswar (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2026)
Ethnomathematics is a field of study that connects mathematical concepts with cultural practices that develop within community life. This study aims to explore the mathematical concepts embedded in post-harvest tobacco activities of the Pandalungan community in Sumber Kalong Village and to develop an ethnomathematics-based Student Worksheet on the topic of direct proportion. This research employed a qualitative method with an ethnographic approach. The research subjects consisted of five tobacco farmers involved in the post-harvest tobacco processing activities and students of MTS Nurul Huda, most of whom come from tobacco-farming families. Data were collected through field observations and in-depth interviews with the farmers. The results of the study show that post-harvest tobacco activities in the Pandalungan community contain various mathematical concepts, particularly in activities related to counting, measuring, and designing. The mathematical concepts identified include direct and inverse proportion, measurement of length and distance, and numerical operations in calculating the fermentation and drying time of tobacco. The concept of direct proportion appears in determining the number of tobacco leaves in certain weight units and in arranging the drying patterns of tobacco leaves. Based on these findings, ethnomathematics-based teaching materials in the form of Student Worksheets (LKS) were developed to assist seventh-grade junior secondary school students (SMP/MTs) in understanding proportional concepts contextually through local cultural activities of the Pandalungan community.